Modern prefab modular system in Malaysia: critical matters and obstacles - Nangkula, Utaberta; Mohd Yunus, Mohd Yazid; Mydin, Md Azree Othuman; Mohd Nawi, Mohd Nasrun (INSInet Publications, 2015)
The construction industry in Malaysia is experiencing a transformation from conventional methods to a more systematic and mechanized method known as prefab system. Each state in Malaysia is currently examining the developments of the prefab system and its potential to overcome the shortages of housing accommodations in this country. The Malaysian government, involved through its agency, the Construction Industry Development Board (CIDB) has been persistently pushing the construction industry to utilize of the prefab method of construction since the year 2003. It is a part of an incorporated endeavour to further improve the aptitude, potential, effectiveness and competitiveness of the industry as well as to diminish the industry's dependence on foreign labours. This is also an attempt in the Malaysian construction industry to encourage positive inroads in matters related to construction-site safety with regards to a working environment which is cleaner, more convenient and more organized. This production is also mentioned as being able to provide more protection to the environment as it secures the sustainability of the industry. This paper will discuss on some current matters related to the execution of prefab system and main barriers towards success of this construction type in Malaysia.